Heavy metal uptake by plants from wastewater of different pulp concentrations and contaminated soils. (10th May 2021) - Shojaei, Saeed; Jafarpour, Amir; Shojaei, Siroos; Gyasi-Agyei, Yeboah; Rodrigo-Comino, Jesús
Abstract: There is a lack of information on the extent of mineral extraction by plants from wastewater in arid and semi-arid environments in developing countries. This research assesses the performance of Alhagi and Mallow plant species for the absorption of heavy metals around the tailings dam of a copper mine in Iran. The industrial wastewater, known as the pulp, from the copper mine site has different concentrations of heavy metals. In a laboratory setting the plants were cultivated and irrigated with different pulp concentrations (0, 20, 40, 60, 80, and 100%) in water. Heavy metals (chromium, manganese, cadmium, and lead) accumulation in the aerial parts and roots of the plants, and the in-situ soil around the tailings dam, were measured using an atomic absorption spectrometer. Soil mapping based on geostatistical methods was also conducted to show the spatial pattern of the contaminants in the surrounds of the tailings dam. Our results demonstrated that heavy metals accumulation was higher in the roots than in the aerial parts, and chromium and cadmium uptake by the Alhagi plant was higher than by the Mallow. The soil mapping showed that cadmium, lead and manganese had a higher dispersion compared to chromium, a high percentage being concentrated in some hotspots. Alhagi and Mallow plants, therefore, have a high potential to remediate heavy metal contaminated areas around the tailings dam and are recommended for widespread use. However, frequent plant harvesting should be encouraged to help reduce the migration of heavy metals from the contaminated soils into the surrounding environment. This research contributes to cleaner industrial production in non-developing and developing countries. Graphical abstract: Image 1 Highlights: Minesites show high concentration of heavy metals that affect natural ecosystems. Heavy metals accumulation was higher in the plant roots than in the aerial parts. Cr and Cd uptake by the Alhagi plant was higher than by the Mallow plant. Cd, Pb, and Mn show a higher spatial dispersion compared to Cr, and in hotspots.